High-resolution array CGH of metanephric adenomas: lack of DNA copy number changes - Szponar, Adrianna; Yusenko, Maria; Kovacs, Gyula (Histopathology, 2010)
Szponar A, Yusenko M V & Kovacs G (2010) Histopathology56, 212-216 High-resolution array CGH of metanephric adenomas: lack of DNA copy number changes Aims: Previous karyotyping and fluorescence in situ hybridization analysis of metanephric adenomas (MAs) has yielded controversial data. The aim of this study was to detect small genomic alterations, if any, specific to MAs by applying high-resolution oligoarrays. Methods and results: DNA extracted from paraffin blocks of six metanephric adenomas was hybridized onto Agilent oligoarrays with ∼43 000 in situ synthesized 60-mer oligonucleotide probes that span coding and non-coding sequences with an average spatial resolution of ∼35 kb. None of the metanephric adenomas showed DNA copy number changes. To confirm our results, DNA extracted from the paraffin block of a chromophobe renal cell carcinoma (RCC) was simultaneously hybridized to one of the four arrays on the same slides as an internal control. The chromophobe RCC showed loss of several chromosomes but no alteration was seen in MAs. We have confirmed the negative results by dye-swap and sex mismatch hybridization experiments. Conclusions: Our high-resolution oligoarray analysis indicates that metanephric adenomas lack DNA copy number alterations. This finding may help to differentiate between metanephric adenomas from Wilms’ tumour and papillary renal cell adenoma with overlapping phenotype.
Erstmals am 23 December 2009 online veröffentlicht
Gesehen am 08.09.2023